Peran Katalog dalam Pameran Seni Rupa Makna Murni: Lintas Batas 19 - Saputri, Deta Anggara Wahyu; Ruta, I Made; Jodog, I Made (Program Studi Seni Murni ISI Bali, 2023)
Starting from the author's ignorance of exhibition cataloging. However, when I visited art exhibitions, I always found a catalog, so I became curious about the role of catalogs in art exhibitions. This prompted the author to examine more deeply the role of an art catalog and try to . The problem is how the catalog plays an important role in an exhibition. In the process of making it, the writer uses the method obtained from the MBKM process. The purpose and benefits are to show how a catalog plays a role in an art exhibition and to develop the creativity of writers in using digital media. In the process of making a catalog the author uses the creation method which includes several stages, namely observation, data collection, exploration, the process of creating. From this process the author produced an exhibition catalog in which there were 9 layouts of the contents of the fine art exhibition catalog. It can be concluded that the author creates works based on his interest in catalogs, with ideas originating from phenomena captured at the Rudana Museum and reading reference sources from the internet. At the processing stage the author refers to the results of the MBKM. Of all these processes are expected to find identity in the work.